Proceedings of the Third Symposium on Information Interaction in Context 2010
DOI: 10.1145/1840784.1840810
|View full text |Cite
|
Sign up to set email alerts
|

Using a concept map to evaluate exploratory search

Abstract: Users often conduct exploratory searches on the Web to solve complex problems, but how for evaluating the effectiveness of a search, especially in a user-centered approach, remains an open question. We propose a user-centered method to evaluate the effectiveness of an exploratory search by focusing on the change in the users' mental representations of a topic during their exploratory search on the Web. This was done by comparing the concept maps depicted before and after each users searching. Thirty-five under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Cole et al (2007) focused on how the students' mental model diagrams for a topic were represented in an early exploration stage of the informationseeking process, and they suggested a 12-category classification schema of the mental models. Egusa et al (2010) investigated how a user's concept map differs before and after a search and how the differences between the topics, scenarios, and browser types influence the user's concept map. A comparative analysis of the concept maps between the pre-and post-search maps indicated that users significantly changed their knowledge structures on a topic through an exploratory search.…”
Section: Introductionmentioning
confidence: 99%
“…Cole et al (2007) focused on how the students' mental model diagrams for a topic were represented in an early exploration stage of the informationseeking process, and they suggested a 12-category classification schema of the mental models. Egusa et al (2010) investigated how a user's concept map differs before and after a search and how the differences between the topics, scenarios, and browser types influence the user's concept map. A comparative analysis of the concept maps between the pre-and post-search maps indicated that users significantly changed their knowledge structures on a topic through an exploratory search.…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of concept maps [20]. For example, task demands concept maps demand students to generate their concept maps (students can be asked to fill-in a skeleton map, or construct a map from scratch, or talk about the relation between concepts).…”
Section: Assessment Tools In Lifelong Learningmentioning
confidence: 99%
“…Task constraints concept maps are characterized by the restrictiveness of the task (e.g., students may or may not be asked to construct a hierarchical map, or to use one or more links between concepts, or to provide the concepts for the map). Task content structure concept maps require the intersection of the task demands and the constraints of the structure of the subject-domain to be mapped (e.g., there is no need to impose a hierarchical structure if the content structure is not hierarchical) [20].…”
Section: Assessment Tools In Lifelong Learningmentioning
confidence: 99%
“…Egusa et al [3] investigated how a user's concept map differs before and after a search and how the differences between the topics, scenarios, and browser types influence the user's concept map. A comparative analysis of concept maps between pre-search and post-search maps indicated that users significantly changed their knowledge structures for a topic through an exploratory search.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies [3,9,10] have only analyzed the changes of concept maps before and after searching. Therefore, these studies could not exclude the possibility of the influence of instructions or time-dependent changes.…”
Section: Introductionmentioning
confidence: 99%